Histological changes of liver tissues and serobiochemical relation in does with pregnancy ketosis - Azmi, Amirul Faiz Mohd; Ghani, A.A.A.; Saadan, A. S.; Mokrish, A.; Lai, K. S.; Zamri-Saad, M.; Zuki, A. B.; Hassim, H. A. (Jurnal Ilmu Ternak dan Veteriner, 2016)
The histological changes of the liver in does with pregnancy ketosis were characterized. Twenty pregnant does at day 80 of pregnancy were used for this experiment. A total of 10 does were fed on grass (napier) and goat concentrate with water ad libitum consider as healthy pregnant goat, and another 10 ten were showed clinical and subclinical signs of ketosis consider as unhealthy pregnant doe. Liver biopsies were performed when clinical signs appear. Beta-Hydroxybutyrate (BHBA), free fatty acid (FFA), and glucose were dosed. Histological preparation revealed similar incidence and intensity of mild liver steatosis with lower cellular vacuolation in hepatocyte presence in healthy late pregnant does. Almost all of pregnant does with ketosis state (n=8/10) had large amount of small lipid droplets in almost every hepatocyte over the whole liver acinus with higher number of cellular vacuolation, and related with higher BHBA and FFA levels while low in glucose levels.Key Words: Beta-Hydroxybutyrate, Does, Free Fatty Acid, Liver Biopsies, Pregnancy Ketosis